Analisis Perspektif Guru terhadap Keterampilan Komunikasi Sosial Siswa - Fawzi, Mochamad Ikbal; Kurniati, Hera; Maftuh, Bunyamin; Somantri, Mubarok (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2025)
This study aims to analyze the teacher's perception of students' social communication skills in IPAS (Natural and Social Sciences) learning. The research subject is a fifth-grade teacher who teaches IPAS at a public elementary school in the Bandung city area. Data collection techniques were carried out through interviews, observations, and document studies. The data analysis technique used in this study follows the method by Miles & Huberman, which consists of data reduction, data presentation, and conclusion or verification. The results of the study show that the teacher pays attention to students' social communication skills during the learning process, although some indicators have not yet been fully met. The conclusion drawn is that students' social communication skills are influenced by various factors, both from the students' backgrounds and from the learning process implemented by the teacher. In this context, the teacher's role during learning is crucial in developing students' social communication skills.